A sensitive and selective LC–MS/MS method for quantitation of ivermectin in human, mouse and monkey plasma: clinical validation. (16th October 2018) - Chhonker, Yashpal S; Ma, Liping; Edi, Constant; Murry, Daryl J
Aim: A sensitive and selective LC–MS/MS method was validated for quantitation of ivermectin (IVM) in plasma.Method: The IVM was extracted from plasma using solid-phase extraction with C-18 cartridges. Separation of analytes was achieved on an ACE C18 column with isocratic elution using 0.1% acetic acid and methanol: acetonitrile (1:1, v/v) as mobile phase. The IVM was quantitated using electrospray ionization operating in negative multiple reaction monitoring mode.Results: The MS/MS response was linear over the concentration range from 0.1–1000 ng/ml. The method for human plasma was validated as per US FDA guidelines. The LC–MS/MS method is sensitive, reproducible, has easy sample preparation and is suitable for IVM quantitation in clinical samples.